PENDEKATAN DALAM PENENTUAN HUTAN DESA BUNTOI, KABUPATEN PULANG PISAU, KALIMANTAN TENGAH - N M Heriyanto (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2017)
Approach in determining village forest has been done by government through Decree of Minister of Forestry Number SK.586/Menhut-II/2012 dated 17 October 2012, covering peat swamp forest of approximately 7,025 hectare in Buntoi Village, Pulang Pisau, Central Kalimantan. In this study, permanent plot of one hectare was randomly selected at that location. The results showed that, biomass and carbon content of forest stand with diameter ≥2 cm was 113.63 ton/hectare or 56.81 ton C/hectare. Forest stand with heterogeneous biomass and heterogeneous species or high diversity will absorb CO2 and produce O2 in the air, so the forest will help in climate change. Forest village became a compromise on the claim of customary forest recognition which until now has not been resolved. The core of the village forest is that communities can manage forests legally for the welfare of rural people and sustainable environments. The designation of forest areas into village forests is appropriate with the indicator as there are no illegal logging, forest fires and relatively good forest conditions.